Characteristics and outcomes of community health worker training to improve the prevention and control of cardiometabolic diseases in low and middle-income countries: a systematic review - Seneviratne, Shilanthi (2023)
Community health workers (CHWs) play an important role in controlling non-communicable diseases in low- and middle-income countries. The aim of this review was to describe the characteristics and outcomes of CHW training programs that focused on the prevention and control of cardiometabolic diseases in low- and middle-income countries (LMICs). Medline, CINAHL Complete, Academic Search Complete, Directory of Open Access Journal, ScienceDirect, ERIC, Gale Academic, and OneFile). Studies that described the training programs used to train CHWs for prevention and control of cardiovascular diseases and type2 diabetes mellitus in LMICs. Only studies that evaluated the outcomes of training programs in at least one of the 4 levels of Kirkpatrick's training evaluation model were included in the review. CHWs who underwent training focused on the prevention and control of cardiovascular disease and type 2 diabetes mellitus. We summarized the resulting evidence using qualitative synthesis through a narrative review. Training outcomes were assessed in relation to (1) CHW reactions to training, their degree of learning, and their behaviors following training, and (2) changes in biochemical and anthropometric indicators in target populations following the CHW program implementation. PROSPERO (CRD42020162116). Thirty-two studies were included. Methods used to train CHWs included: face-to-face lectures, interactive group activities, and blended teaching with online support. Training focused on identifying people with elevated risk of cardiometabolic diseases and their risk factors as well as supporting people to adopt healthy lifestyles. Many studies that utilized trained CHWs did not publish CHW training methods and evaluations, and therefore could not be included in this study. Training programs resulted in an increase in knowledge and skills among CHWs demonstrating that there are certain activities that can be shifted to CHWs following training.